First Isolation of a Rabid Bat Infected with European Bat Lyssavirus in Luxembourg. (30th December 2013) - Servat, A.; Herr, J.; Picard‐Meyer, E.; Schley, L.; Harbusch, C.; Michaux, C.; Pir, J.; Robardet, E.; Engel, E.; Cliquet, F.
Summary Rabid bats are regularly reported in Europe, especially in countries that have implemented a bat surveillance network. In May 2013, bat rabies was evidenced for the first time in Luxembourg (southern city of Differdange). The rabies virus, an EBLV‐1b strain, was diagnosed in a serotine bat that bit a 29‐year‐old male person while he was asleep. The man received rapidly a post‐exposure RABV treatment and was put under strict medical supervision.